A novel technical analysis and survey on disaster robots for flood search and rescue operations - Duvvuru, Rajesh; Jagadeeswara Rao, Peddada; Narasimha Rao, Gudikandhula; Rayachoti, Eswaraiah; Boyidi, Suribabu; Prathyusha, Kodamala (Bulletin of Electrical Engineering and Informatics, 2025)
The advance in human-robot interaction brings out novel applications of the disaster rescue operations. Especially, the concept of search and rescue (SAR) assisted robot operations plays an extensive role in the natural hazards, such as earthquake and wild fires. Particularly, the SAR operations in the water-based drowning due to floods and boat capsize disaster are expensive and not fast. This paper presents a survey on various SAR based remotely operated vehicle’s (ROV) related to airborne, under and surface of the water, such as unmanned marine vehicles (UMV) and unmanned aerial vehicles (UAV). In addition, the performance analysis of each UMV such as EyeROV TUNA, Saif Seas, iBubble, DTG3, Trident, Fathom One and SEAOTTER-2, is listed which helps to select the right UMV for the rescue operation at different water depths. Also discussed various SAR based UAVs like DJI Phantom-MAVIC 2, YUNEEC-H520 Hexacopter, Microdrones MD4-1000, DSLRProsMatrice 210 RTK V2 and AltiGator’sXena Drone for the flood and boat capsize operations. However, the usage of Syma X8 Pro UAV for the flood operations are worthy than Sea King SAR Chopper, which is a cost-effective operation.